Kto est' kto . Kto est' kto . Who is Who? . Кто есть кто - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by the state television (Moscow) in the USSR and recorded by the Radio Liberty Monitoring Unit in Munich as part of their effort to track and analyze the official media of the republics of the Soviet Union. Передача государственного телевидения (Москва, СССР) была записана отделом мониторинга радиостанции Свобода (Мюнхен) как часть проекта по анализу официальных средств информации республик Советского Союза. Discussion on deputies' work and the political situation in the USSR. The viewers ask question during the live broadcast. Featured in the program: Vol'skii, Arkadii Ivanovich (People's Deputy); Alksnis, Viktor (People's Deputy) Contributors: Fesunenko, Igor' Sergeevich (Anchor) Обсуждение деятельности депутатов и политической ситуации в СССР. Вопросы задают телезрители в прямом эфире. В программе участвуют: Вольский, Аркадий Иванович (Народный депутат); Алкснис, Виктор (Народный депутат) Создатели: Фесуненко, Игорь Сергеевич (Ведущий/Ведущая)